Medium- to Long-Term Results of the Nexgen Legacy Posterior Stabilized Fixed-Bearing Knee Replacement - Arikupurathu, Oommen Mathew; Johnston, Linda; MacInnes, Alasdair; Nicol, Graeme; Nassif, Manhal (The Journal of Knee Surgery, 2019)
The NexGen legacy posterior stabilized (LPS) prosthesis was introduced in 1997 after many design changes to its predecessor, the Insall–Burstein II prosthesis. However, there have been no reported long-term studies on the performance of this implant. Prospectively, collected data from a local database comprising primary total knee replacements (TKRs) with LPS between 1997 and 2002 was analyzed. All implants were fixed with cement. Patients were followed up at 1, 3, 5, 7, and 10 years, with patient satisfaction, range of movement, and Knee Society score (KSS) assessed. A total of 621 primary TKRs were analyzed with an average follow-up of 11.25 years (9.15–14.55). The mean age was 69.53 years. The mean KSS was 88.97 and mean flexion increased from 88.3 to 103.5 degrees at 10 years. Kaplan–Meier's analysis revealed a survivorship of 96.5% with revision for any reason as the end point and 98.9% if aseptic loosening was the reason for revision at 14 years. This study revealed excellent mid- to long-term results with the NexGen LPS prosthesis.
Keywords: NexGen LPS; knee; score; Kaplan–Meier; survivorship